Wear characteristic of several commercial wrought aluminium alloys against tool steel - Mariyam Jameelah Ghazali (2006)
Aluminium alloys are increasingly being used in tribological applications, often in composite form, but to date no systematic work has been undertaken on optimising the matrix composition. In particular, it is not clear whether a work-hardened, a precipitation hardened or dispersion hardened matrix is optimum. Accordingly, the dry sliding wear behaviour of four aluminium alloys (A2124, A6092 (both precipitation hardened), A3004 (dispersion hardened) and A5056 (work hardened) was investigated against an M2 steel counterface in the load range 23-140N and at a fixed sliding speed of 1 ms-1. Severe wear was observed for all alloys, with domination of transfer of Fe from the counterface for all alloys, which resulted in the formation of a mechanically mixed layer. The relationship between alloy composition, deformation below worn surface and wear resistance is discussed